2022
DOI: 10.1155/2022/6609531
|View full text |Cite
|
Sign up to set email alerts
|

A Hospital-Based Study on the Prevalence of Keratoconus in First-Degree Relatives of Patients with Keratoconus in Central China

Abstract: Purpose. The present study investigated the prevalence of keratoconus (KC) among first-degree relatives of KC patients in Central China. Methods. From July 2018 to March 2022, 661 first-degree relatives of 384 KC patients were included in the present study. Corneal tomography, uncorrected distance visual acuity, manifest refraction with corrected distance visual acuity, intraocular pressure, slit-lamp microscopy, and fundus examination were performed. The diagnosis of KC was based on the Belin/Ambrosio enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In a Chinese report, the prevalence of keratoconus in first-degree relatives was about 9% and the CLEK study found a positive family history of keratoconus in 13% of the patients. [33][34][35] The association between allergy/atopy and keratoconus has been well documented in several studies. 14,31 Eye rubbing habit has been considered one of the major risk factors for disease development in several studies 13,36 ; here, two patients (18%) with keratoconus reported eye rubbing habit, which was found in 5% of normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In a Chinese report, the prevalence of keratoconus in first-degree relatives was about 9% and the CLEK study found a positive family history of keratoconus in 13% of the patients. [33][34][35] The association between allergy/atopy and keratoconus has been well documented in several studies. 14,31 Eye rubbing habit has been considered one of the major risk factors for disease development in several studies 13,36 ; here, two patients (18%) with keratoconus reported eye rubbing habit, which was found in 5% of normal subjects.…”
Section: Discussionmentioning
confidence: 99%